Molecular phylogeny and morphology of Cunninghamella guizhouensis sp. nov. (Cunninghamellaceae, Mucorales), from soil in Guizhou, China - Zhang, Zhi-Yuan; Zhao, Yi-Xuan; Shen, Xin; Chen, Wan-Hao; Han, Yan-Feng; Huang, Jian-Zhong; Liang, Zong-Qi (Phytotaxa, 2020)
During a survey of keratinolytic fungi in China, three Cunninghamella strains were isolated. Phylogenetic analyses of ITS and ITS+LSU+EF-1α sequence data showed that these strains constitute a new species related to C. blakesleeana, C. bigelovii, C. multiverticillata and C. phaeospora. The new species differs from C. multiverticillata and C. phaeospora in the shape and size of its teminal and lateral vesicles and can be distinguished from C. blakesleeana and C. bigelovii by the absent of zygosporangia, and the shape and size of it sporangioles. The results of phylogenetic and morphological analyses indicate that the three strains are a new species of Cunninghamella. Descriptions and illustrations of this novel species are provided in this paper.